2005
DOI: 10.1002/bip.20238
|View full text |Cite
|
Sign up to set email alerts
|

A well‐defined amphipathic conformation for the calcium‐free cyclic lipopeptide antibiotic, daptomycin, in aqueous solution

Abstract: Daptomycin is a 13-residue cyclic lipopeptide with Ca 2ϩ -dependent bactericidal activity against a variety of high-risk pathogens. Ring closure in daptomycin is via an ester linkage between the side chain of-free daptomycin is reported to lack a well-defined conformation (D. Jung, A. Rozek, M. Okron, and R. E. W. Hancock, Chemistry & Biology, 2004, Vol. 11, pp. 949-957) or is suggested to populate an alternate conformation (L.-J. Ball, C. M. Goult, J. A. Donarski, J. Micklefield, and V. Ramesh, Organic & B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 22 publications
4
51
0
Order By: Relevance
“…39 From the findings described in section 6.3, one would expect apo-daptomycin to exist mainly as aggregates under these conditions. However, these workers reported that they avoided aggregation by adding solid daptomycin to a degassed buffer in successive small portions, each of which was allowed time to completely dissolve prior to the next addition.…”
Section: Solution Structure Of Apo-daptomycinmentioning
confidence: 92%
See 2 more Smart Citations
“…39 From the findings described in section 6.3, one would expect apo-daptomycin to exist mainly as aggregates under these conditions. However, these workers reported that they avoided aggregation by adding solid daptomycin to a degassed buffer in successive small portions, each of which was allowed time to completely dissolve prior to the next addition.…”
Section: Solution Structure Of Apo-daptomycinmentioning
confidence: 92%
“…This question has been studied with 1 H-NMR 36,39 and optical methods. 40 In the absence of calcium and at pH 7.4 or higher, daptomycin aggregation is minimal or absent at millimolar concentrations, whereas under acidic conditions aggregates may form at concentrations as low as 0.12-0.2 mM.…”
Section: Aggregation Of Free Daptomycin In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is only limited knowledge of the lipopeptide molecular mode of action, a few key properties have been described. A number of lipopeptides tend to aggregate into oligomers and micelles and can readily interact with the cytoplasmic membrane via their hydrophobic moieties [28,59]. Thus, these types of compounds with their unusual structures that act rapidly on membrane integrity rather than on other vital processes are a growing source of concern in modern medicine and might perhaps hold promise for the development of a new generation of antibiotics [60].…”
Section: Potential Applications Of Surfactinsmentioning
confidence: 99%
“…Daptomycin, however, exhibits a different mechanism of action, as Ca 2ϩ helps daptomycin to interact with and aggregate in the membrane (2,15,19,24), leading to membrane depolarization and eventual bacterial cell death (28). Nevertheless, the presence of Ca 2ϩ had less of an effect on the activity and secondary structure/membrane interaction of MX-2401 than on those of daptomycin, consistent with its different mechanism of action, inhibiting the biosynthesis of the cell wall and teichoic acid precursors (25).…”
mentioning
confidence: 99%